New Zealand media camouflage political lobbying - Catherine Strong (Asia Pacific Network, 2017)
Political lobbyists are a part of government decision-making processes, and many countries have stringent regulations to ensure their activities are somewhat transparent, especially as some use ethically questionable tactics. In New Zealand, however, there are no similar legislative regulations and lobbyists can stay undetected while trying to influence policymaking.  More concerning, however, is that the results of this study indicates that lobbyists are also able to skirt around scrutiny in New Zealand media because of current journalism practices.  This research’s content analysis indicates the media neglects to identify lobby organisations, thereby allowing them to operate without detection of their agenda, leaving the public unaware of who is influencing decision makers.